Analysis of aerobic testing in basketball referees and heart rate recovery time - Ramiro Marques Inchauspe; Alejandro Vaquera; Pablo Morales Barbian; Flávia Renata de Almeida; Cassiano Teixeira (Universidade Federal de Santa Catarina, 2020)
The study analyzed the physical conditioning and the time of recovery of the maximum heart rate of 12 international referees being used the test of 20 meters with beep to evaluate the cardiorespiratory conditioning, with the frequency to control the recovery time of the maximum cardiac post test. The majority of the referees obtained a recovery of heart rate greater than 50% in 3 minutes, were those that reached the levels of good to excellent in the table of maximum Vo2. Even with some factors influencing their physical performance most of the referees were able to complete the aerobic test and obtained a good recovery of the heart rate, the others that failed to reach the test goal had the HR recovery in 3 minutes much lower than expected, thus highlighting the association of the maximum VO2 level between good and excellent with the recovery of the heart frequency.